PENGAWETAN WARNA KAYU TUSAM (Pinus merkusii) DAN PULAI (Alstonia sp.) DENGAN MENGGUNAKAN BAHAN DASAR DISINFEKTAN - Barly; Agus Ismanto; Dominicus Martono; Abdurachman (Jurnal Penelitian Hasil Hutan, 2012)
Wood color can vary much between species but the variations tends to be smaller within the same species. Noticeable deviations in color at timber surface or in the core of the same board my cause problems in timber trading or in final product's appearance. Undesirable discoloration often develops during wood drying process. The research aims to study natural color changes of Pulai (Alstonia sp.) and Pine (Pinus merkusii). Prevention of wood color change is undertaken by using active ingredients of benzylkonium chloride (A and D), phenol (B and C), creselic acid (E), sodium bypochlorite (F) and methylen-bis-thiocyanate (G). The treated wood samples together with their controls were then kept in three different conditions, i.e. conditioning room at 70 RH and temperature of 18 C, in the terrace and in the oven with temperatures of 60 C and 120 C. The test results demonstrate that the bigbest brightness (L") was obtained at Pulai the wood surface and inside the wood block using formulation of D, namely 87.3 and 89.3 with a total value of the brightness variation (AL) -6.7 and -4.7. However, the bigbest brightness of Pine wood was acchiered using formulation, namely 83.5 and 80.0 with a total variation of brightnest of -10.5 and-14.0. These value swere obtained from samples stored in low temperature and bumidity (air conditioned).